La responsabilidad social empresarial y el crecimiento sostenible en el sector turístico en la parroquia Salinas de Guaranda. - Masabanda Duran, Nancy Eliana (2025)
This research study is about how Corporate Social Responsibility (CSR) influences the sustainable growth of the tourism sector in the Salinas de Guaranda parish. CSR not only improves the image of companies, but also helps to protect the environment and improve the quality of life of local communities. Its application helps to generate a balance between economic development and environmental protection, thus ensuring a more responsible and beneficial tourism for the region. In this study, some problems have been revealed to tourism companies, such as lack of clear strategies to balance economic growth with stability, lack of financial resources and lack of training in the field of CSR. To obtain information, surveys and interviews with managers and companies of companies that allow us to learn about the reality of tourism in Salinas de Guaranda and the ability to improve the introduction of sustainable activities. The results show that cooperation between companies, communities and governments is very important in promoting sustainable tourism. Despite the achievement, the lack of awareness of the importance of CSR and the poor implementation of structural strategies to limit its impact. That is why it is extremely important to strengthen training programs and encourage it to encourage many companies to accept a responsible and sustainable practice. It is determined that a management approach based on corporate social responsibility is required to promote more responsible tourism in Salinas de Guaranda, ensuring economic progress that benefits everyone without compromising the future of the environment and the community. The implementation of defined policies and educational initiatives in sustainability for the area's business owners and employees will be essential to achieving harmonious and sustainable growth in the region.